Effect of DNA sequence of Fab fragment on yield characteristics and cell growth of E-coli - Kulmala A; Huovinen T; Lamminmaki U (NATURE PUBLISHING GROUP, 2022)
Codon usage is one of the factors influencing recombinant protein expression. We were interested in the codon usage of an antibody Fab fragment gene exhibiting extreme toxicity in the E. coli host. The toxic synthetic human Fab gene contained domains optimized by the "one amino acid-one codon" method. We redesigned five segments of the Fab gene with a "codon harmonization" method described by Angov et al. and studied the effects of these changes on cell viability, Fab yield and display on filamentous phage using different vectors and bacterial strains. The harmonization considerably reduced toxicity, increased Fab expression from negligible levels to 10 mg/l, and restored the display on phage. Testing the impact of the individual redesigned segments revealed that the most significant effects were conferred by changes in the constant domain of the light chain. For some of the Fab gene variants, we also observed striking differences in protein yields when cloned from a chloramphenicol resistant vector into an identical vector, except with ampicillin resistance. In conclusion, our results show that the expression of a heterodimeric secretory protein can be improved by harmonizing selected DNA segments by synonymous codons and reveal additional complexity involved in heterologous protein expression.